Frequency of gall bladder carcinoma in cholecystectomies for symptomatic cholelithiasis - Muhammad Amar Qudeer; Syed Asghar Naqi; Muhammad Zeeshan Sarwar; Hafiza Amina Mujahid (Journal of the Pakistan Medical Association, 2020)
It was a Letter to the Editor to find out the frequency of carcinoma gall bladder in patients which were presented with symptomatic cholelithiasis. Carcinoma of the gallbladder is a rear malignancy with 5 year survival rate of 5%. Carcinoma gall bladder is the most common billiary tract malignancy, it is also 5th most common in gastrointestinal malignancies 1. In Pakistan the incidence of carcinoma gallbladder among patients having symptomatic cholelithiasis is 6 to 28%2. Patients with symptomatic gall stones had more risk for developing carcinoma gallbladder as compared to asymptomatic gall stones. Large stones in cholelithiasis are more dangerous than small stones as stone size reaches >3cm risk increases upto 10 fold. Gallbladder polyps >10mm, calcified(porcelain) gallbladder, choledochal cyst, seclerosing cholangitis, anomalous pancreaticobillary junctions and exposure to carcinogens are other risk factors3. Continuous...